Psychological Dynamics In The Changing Of Bullying Victims Into Bullies At Student In Islamic Boarding School - Sigit Nugroho; Seger Handoyo; Wiwin Hendriani (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Bullying case was one of the problems conducted in school that became an international concern. Bullying occurrence in school was not limited to regular school but also in boarding school, particularly in islamic boarding school; thus, this phenomenon had a higher chance to occur in boarding school due to seniority. It was also found that the bullies were previously had the experiences as the victims. According to this phenomenon, a qualitative study was held to formulate the substantial theory about the psychological dynamics of the victim becoming bullies, particularly in islamic boarding school context. This study conducted the systematic grounded theory. The data was collected through in-depth interviews and observations toward nine main participants, and some supported participants and analyzed with constant comparative technique. The finding of this study was The Dynamic of Bullying: The Victims Become Bullies, which contained six phases: 1) Become the victims, 2) Aggrieved phase, 3) Frustration phase, 4) Maladaptive coping phase, 5) Trial phase, 6) Become the bullies. This dynamic explained the psychological dynamics in the victims who become bullies. Some interesting findings found in the fourth phase, the maladaptive coping phase, in which the victims decide whether to be adaptive or maladaptive to bullying activity. The alternate in the adaptation phase indicated that the shifting role of victims to bullies could be prevented. Psychological support programs, both preventive and curative way, could be beneficial to prevent the possibility of the victim becoming bullies. The preventive program could prevent the victims from becoming bullies, and the curative program could help the victim heal the trauma of bullying.